Hybrid recommendation system of intelligent captioning using deep learning networks - Wasi, Ahamed Al; Fahim, Ezazul Haque; Inova, Nishat Tasnim; Fahim, Abdullah Al; Preeti, Taghrid Tahani (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.